A Bayesian Approach for Detection of Isotropy Violation of a Random Field Over a Sphere. Issue 1 (May 2017) - Souradeep, Tarun; Das, Santanu; Wandelt, Benjamin D.
We present a general method for estimating the isotropy violation of random fields on a sphere using a Bayesian formalism. We use Bipolar Spherical Harmonic (BipoSH) representation of general covariance structure on the sphere. Our approach promises to provide a robust quantitative evaluation of the evidence for SI violation-related anomalies in the CMB sky by estimating the BipoSH spectra along with their complete posterior.